Venoarterial extracorporeal membrane oxygenation is a feasible option for patients with pregnancy-associated diagnoses who require mechanical circulatory support - Trishna Parikh; Sabiha Armin; Saad Afzal Khan; Adishwar Rao; Akriti Agrawal; Dev Patel; Bindu Akkanti (Resuscitation Plus)
Background: Venoarterial extracorporeal membrane oxygenation (VA-ECMO) is used in patients with cardiopulmonary collapse, but data regarding its use in pregnancy is limited. We aimed to identify the clinical characteristics and predictors of in-hospital mortality in female patients requiring VA-ECMO, including evaluating the role of pregnancy. Methods: In this cross-sectional study, a cohort of female patients aged 19–45 years who required VA-ECMO were identified from the National Inpatient Sample from 2018 to 2021 and further stratified according to presence of pregnancy-associated diagnoses. Baseline characteristics were compared using Pearson chi-square test and Wilcoxon rank-sum test for categorical and continuous variables, respectively. Multivariate analysis using a logistic regression model was performed to identify predictors of in-hospital mortality in the entire cohort. Subgroup analyses were done in patients with coronavirus disease 2019 (COVID-19). Results: Of 2,010 female patients requiring VA-ECMO, 255 (12.7%) had a pregnancy-associated diagnosis. Cardiogenic shock was more common among patients without a pregnancy-associated diagnosis. There was no difference in in-hospital mortality between the two groups (p = 0.15). Infectious complications (adjusted odds ratio [OR]: 1.72 [1.01–2.93], p = 0.05) were positively associated with in-hospital mortality. Pregnancy-associated diagnoses were not associated with survival (OR: 0.51 [0.21–1.25], p = 0.14) in the entire cohort or in a subgroup of patients with COVID-19 (OR: 0.30 [0.01–19.01], p = 0.52). Conclusions: VA-ECMO remains a feasible option in patients with pregnancy-associated diagnoses requiring mechanical circulatory support. Infection control is required to decrease the associated in-hospital mortality.